An Analysis of Junior High School Students Metacognitive Ability for solving Numeration Problem - Tri Nova Hasti Yunianta; Nanda Pravita Sari (Jurnal Pendidikan Matematika IKIP Veteran Semarang, 2023)
The metacognitive ability of students is low in using and applying the knowledge that has been learned, managing the information obtained, choosing the right strategy, and developing an effective strategy as the basis for carrying out research. This qualitative study aims to describe the metacognitive abilities of junior high school students in solving numeracy problems related to Numbers Data & Uncertainty materials. The research subjects were three grade VIII students of SMP Negeri 1 Salatiga who were selected by purposive sampling technique. The criteria for selecting the subject are able to solve questions 1?4 using appropriate, communicative, and commitment strategies to become a subject. The data were collected through a written test in the form of AKM (Minimum Competency Assessment) simulation numeration questions and interviews according to indicators of metacognitive ability. There are aspects of metacognitive abilities that are observed, namely planning, monitoring, and evaluating. The results of the study of the three subjects carried out two indicators of the planning, namely students could plan the objectives to be carried out and sequence the stages of the strategy to be carried out. Indicators carried out by the subject at the monitoring are that students can perform careful calculations and indicators that have not been implemented are students checking answers from the results and correcting errors. In the evaluation three subjects carried out two indicators, namely, the students were able to assess the results and re-evaluate the objectives. Keywords: Metacognitive, Metacognitive Ability, Numeracy